Pengaruh Privasi, Keamanan, Kepercayaan, Dan Pengalaman Terhadap Niat Untuk Bertransaksi Secara Online - Susilowati, Dewi, Yuli Tri Cahyono, M.M.,Akt, CA (2016)
Internet as a computer network can be used as a medium of trade in the era of globalization. The purpose of this study is to examine the influence of privacy, security, trust, and experience on the intention to transact online. Analysis of the data in this study is 100 respondens. Sampling techniques in this study using survey method. The analytical method used is multiple linear regression to test and prove the research hypothesis. The analysis results showed that the variables of privacy and trust affect the intent to transact online, while variable security and experience do not affect the intent to transact online. Keyword: privacy, trust, security, experience.